BRINE SHRIMP LETHALITY TEST (BSLT) PADA EKSTRAK AIR KAYU SECANG (CAESALPINIA SAPPAN L.) SECARA IN VITRO - Nathasya Angelia Satya (2022)
Caesalpinia sappan L. is a plant belonging to the Fabaceae family, which has long been known and used as a medicinal plant. Caesalpinia sappan L. wood is known to contain active compounds in the form of brazilin, flavonoids, tannins, alkaloids, saponins, and terpenoids which have antioxidant, anti-inflammatory, antibacterial, antiviral, and anticancer properties. The aim of this study was to determine the lethal concentration (LC50) of the aqueous Caesalpinia sappan L. wood extract using the Brine Shrimp Lethality Test (BSLT) method. LC50 is the concentration value of the compound that causes death in Artemia salina Leach as much as 50%. This study used 4 concentration treatments, namely 1000 ppm, 500 ppm, 100 ppm, and 50 ppm along with negative controls, each of which was repeated three times. Larvae of Artemia salina Leach were used as many as 10 larvae for each concentration and then the larval mortality was observed after 24 hours of treatment. The LC50 value of 322,54 ppm indicates that the aqueous extract of Caesalpinia sappan L. is in the moderately toxic category and has potential as an anticancer compound. Keywords: Caesalpinia sappan L. wood extract, BSLT, Artemia salina Leach, Toxicity, LC50